Chemical Modification of Camelina Oil based Unsaturated Fatty Acid for Renewable Biolubricant Base Stock - Sharma, Neha; Charan Meher, Lekha; Chandra, Krishna; Kumari, Anjali; Bala, Madhu (Asian Journal of Chemistry, 2020)
A green and eco-friendly method for preparation of oleochemicals from Camelina oil was developed for possible application for bio-lubricant basestocks, The steps involved are consisting of epoxidation of Camelina oil based fatty acid followed by further branching with wide range of alcohol such as 2-propanol, n-butanol, isoamyl alcohol and 2-ethylhexanol. These products were evaluated with physico-chemical properties such as acid value, oxirane oxygen content (OOC), hydroxyl value, low temperature properties, viscosity at 40 and 100 °C, viscosity index and characterized by FTIR, 1H NMR. The appearance of peak at 824 cm–1 in the FTIR spectra was due to the formation of epoxy group and broad peak appeared at 3500-3300 cm–1 is for hydrogen bonded O-H stretching vibration of hydroxy group. The 1H NMR spectra showed a signal at 2.9-3.2 ppm region indicated CH-proton attached to the oxygen atom of the both epoxy group for epoxidized product, peaks for newly formed secondary alcohols emerged at 4.25-3.35 in alkoxy derivatives. The Camelina based synthetic product may find application in biolubricants base stock.